2011
DOI: 10.1002/eji.201141291
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the development of acute hepatitis by IL‐23 through IL‐22 and IL‐17 production

Abstract: IL-23 plays a critical role in the expansion of highly proinflammatory Th17 cells secreting . Recently, we demonstrated that Notch signaling drives IL-22 secretion through the aryl hydrocarbon receptor (AHR) and plays a protective role in Con A-induced hepatitis. In this study, we investigated the role of IL-23 in hepatitis using IL-23p19-and IL-17-deficient mice. In WT mice, the injection of Con A induced the upregulation of various cytokines, which included IL-23, IL-22, IL-17, IFN-c and TNF-a. In IL-23p19-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…IL-17A production by CD4 T cells requires IL-23-mediated activation of the transcription factors STAT3 and STAT4 (21,40). Because IL-4 signals through STAT6 (15), we determined the relative contribution of STAT4 and STAT6 in Mmp12 expression during P. murina lung infection.…”
Section: P Murina Lung Exposure Results In the Induction Of Mmp12mentioning
confidence: 99%
“…IL-17A production by CD4 T cells requires IL-23-mediated activation of the transcription factors STAT3 and STAT4 (21,40). Because IL-4 signals through STAT6 (15), we determined the relative contribution of STAT4 and STAT6 in Mmp12 expression during P. murina lung infection.…”
Section: P Murina Lung Exposure Results In the Induction Of Mmp12mentioning
confidence: 99%
“…Moreover, IL-17 secretion by activated T cells upon ConA stimulation promoted TNF-α and IL-6 production by KCs, causing liver damage [100]. Supporting this pro-inflammatory role of IL-17, neutralization or deficiency of IL-17 led to reduced ConA-induced liver damage whereas exogenous IL-17 aggravated it [71,100,102,103]. Nevertheless, the complete role of IL-17 in the pathogenesis of ConA-induced hepatitis remains unclear since an immunosuppressive role was recently described [104].…”
Section: Th17 Cellsmentioning
confidence: 95%
“…Nevertheless, the complete role of IL-17 in the pathogenesis of ConA-induced hepatitis remains unclear since an immunosuppressive role was recently described [104]. By promoting inducible Nitric Oxide Synthase (iNOS) expression in mesenchymal stem cells and induction of cytokine/chemokine gene expression, IL-17 can enhance in vivo immunosuppressive effects in ConA-induced hepatitis [103][104][105][106].…”
Section: Th17 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that IL-22 can upregulate keratinocyte genes for anti-microbial peptides including β-defensins (S100A7, S100A8), CXCL5 and MMP3. [35][36][37] IL-22 can enhance innate immune responses, inducing acute phase proteins in ConA-induced hepatitis, in protecting liver from damage, 38,39 including from fibrosis and chronic hepatitis B infection, 40,41 but little is known about the effect of IL-22 on adaptive immune responses when it is used as a molecular adjuvant.…”
Section: Cloning Of Murine Il-22 and Expression In Bhk Cellsmentioning
confidence: 99%